Invasive pneumococcal disease in the post vaccine era: Case report - Miranda Choque, Edwin Albino H. (2016)
Invasive pneumococcal disease (IPD) is the most severe clinical presentation of infection by Streptococcus pneumoniae. Peru since 2008 includes pneumococcal vaccine in the national immunization schedule. We report a case of a 10 year old girl who goes by emergency showing meningeal signs; in addition, abdominal pain, infiltrated right basal hilum on chest radiography, presence of peritoneal fluid and peritoneal adenopathy in diagnostic imaging support. It is isolated in blood and CSF cultures Streptococcus pneumoniae serotype 11A, no vaccine-strain, being sensitive to ceftriaxone and vancomycin. We recommend the need to know more about the presence of not vaccine pneumococcal serotypes in the clinical and epidemiological context and its pathogenic role in Peruvian population.